Skrining Inhibitor NF-κB Combretum indicum dengan Metode Docking - Samsul Hadi; Amalia Khairunnisa; Sefa Nur Khalifah; Sintya Oktaviani; Sri Oktaviana Sari; Umi Nur Hapifah (Universitas Muhammadiyah Surakarta, 2021)
Nuclear factor kappa B (NF-κB) is a transcription factor that regulates the expression of genes important for innate and adaptive immune responses. NF-κB overactivation is associated with inflammatory diseases such as autoimmune, systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). This study aims to screen the chemical content of C.indicum against NF-κB-inducing kinase inhibitors. There are two methods used in this study, namely through PASSonline and docking. The docking method used was PLANTS. The results of PASSonline compounds that have P.a values above 0.7 weree arachidonic acid, linoleic acid, rutin, methyl urasolate, while the docking scores obtained were asquisqualic acid: -60.0382; arachidonic acid : -100,9410; linoleic acid: -93.8730; routine : -102,9320; methyl urasolate: -47,9166. This negative docking score indicates that the reaction between the compound and the target occurs easily. In conclusion, the compound predicted to have a potential as an inhibitor of NF-κB is Rutin.